FAKTOR- FAKTOR YANG MEMPENGARUHI ADOPSI TEKNOLOGI BUDIDAYA TANAMAN PADI SAWAH DI KECAMATAN KUPANG TIMUR KABUPATEN KUPANG PROPINSI NUSA TENGGARA TIMUR - Wely Yitro Pello; Cokorda Mahardika Putra (Partner, 2021)
This research aimed to find out how lowland rice farming technology is being adopted in East Kupang District (Y), as well as the impact of internal (X1) and external (X2) factors (Y). Multiple linear regression is used to analyze data. The study's findings revealed that Rice Field Cultivation Technology Adoption was High Criteria (74.36%), and Hypothesis Testing compared the t-count and t-table values (2.039) at a significant threshold of 0.05. The results demonstrate that Extension Quality (X2.2) has an external factor (X2) of 2.067, and Farmer Participation in Farmer Groups (X2.3) has an external factor (X2.3) of 4.080, both of which have an effect on Y.Keywords : Paddy Rice, Adoption, and Cultivation